Studi Perilaku Monyet Ekor Panjang (Macaca fascicularis) di Taman Wisata Alam Grojogan Sewu Tawangmangu Karanganyar - Sari, Dewi Puspita; Saputra, Alanindra (Prosiding KPSDA, 2015)
Long-tailed monkeys (Macaca fascicularis) are social primate animals that interact each other. Social interaction done by long-tailed monkeys give rise to different activities of individuals in the population. The purpose of this research was to study long-tailed monkeys behavior in Grojogan Sewu, Tawangmangu, Karanganyar. This research was conducted in Tuesday, November 24th 2014 in Grojogan Sewu, Tawangmangu, Karanganyar. Observational method that used in this research is focal sampling. Determination of sampling points was conducted by purposive sampling so that resulted 8 sampling points (8 individuals of long-tailed monkeys was observed). Observation was done by observing each long-tailed monkeys daily activity until 3 hours with 5 minutes intervals. Result of this research shows that the average percentage of daily activities of the observed long-tailed monkeys are: 2.27% sleeping; 20.76% inactive; 16.78% grooming; 1.99% mating; 32.85% moving; 13.37% eating; 4.97% take caring; 5.26% playing; 0.71% secreting; 0.42% making a voice; and 0.56% agonistic.